1977
DOI: 10.1002/path.1711210403
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the ultrastructural alterations in the pulmonary vessels of rats treated with alphanaphthylthiourea (ANTU) and ammonium sulphate

Abstract: A comparative study of the ultrastructural changes in rat pulmonary vessels was made in two different situtations of increased vascular permeability: one caused by alpha-naphthylthiourea (ANTU) and the other induced by ammonium sulphate (AS). AS had a more destructive effect on the capillaries but showed little alteration in vessels larger than capillaries. ANTU provoked milder ultrastructural lesions but acted on capillaries, arterial and venous structures. In both conditions intravenously injected carbon par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Blebs, sloughing of the endothelium and platelet and leucocyte thrombi, are non-specific responses of lung vessels. They occur in other situations such as immunological pulmonary oedema ( B o b et al, 1973), pulmonary oedema induced by ammonium sulphate and alpha-naphthyl-thiourea (Hatakeyama and Shigei, 1968;Hayes and Shiga, 1970;Machado et al, 1977), snake venom induced vascular injuries (Almeida et al, 1977) and many other situations (Hurley, 1978). In all cases, these alterations indicate severe damage to the lung vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Blebs, sloughing of the endothelium and platelet and leucocyte thrombi, are non-specific responses of lung vessels. They occur in other situations such as immunological pulmonary oedema ( B o b et al, 1973), pulmonary oedema induced by ammonium sulphate and alpha-naphthyl-thiourea (Hatakeyama and Shigei, 1968;Hayes and Shiga, 1970;Machado et al, 1977), snake venom induced vascular injuries (Almeida et al, 1977) and many other situations (Hurley, 1978). In all cases, these alterations indicate severe damage to the lung vessels.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the pattern of fluid accumulation in interstitial tissues might result from fluid leakage from larger vessels within the interstitial space (Whayne and Severinghaus, 1968 ;Iliff, 1971). However carbon labelling studies on pulmonary oedema induced by either ANTU (Bohm, 1966;Cunningham and Hurley, 1972;Machado, Bohm and Padovan, 1977) or pyrrolizidine pyrroles (Hurley and Jago, 1975;Stoner, 1972 Plestina et al, 1977) show that in these types of pulmonary oedema leakage occurs from small vessels-arterioles, capillaries and venules within the alveolar wall (figs. 4 and 5).…”
Section: Liquid Exchanges In the Normal Lungmentioning
confidence: 99%
“…This type of pulmonary oedema seems to be due to increased vascular permeability uncomplicated by concurrent hydrodynamic disturbances. Several ultrastructural and topographical studies have been made of ANTUinduced oedema (Terpitz, 1968;Cunningham and Hurley, 1972;Meyrick, Miller and Reid, 1972;PIestina and Stoner, 1972;Machado et al, 1977). All studies report minor but definite injury to pulmonary vascular endothelium with in non-fatal cases " regenerative " changes 24-48 hr later.…”
Section: Mechanisms Of Pulmonary Oedema Formationmentioning
confidence: 99%
See 2 more Smart Citations